Zusammenhangen and logical atomism in Wittgenstein's tractatus - Dyer, Clive (Rhodes University, Faculty of Humanities, Department of Philosophy, 1982)
Introduction: The argument presented in this thesis is that Wittgenstein's answer to the question - as to how one. proposition can be generated out of another - can show a way in which the reconciliation between logical atomism and Zusammenhangen becomes obvious. In the Preliminaries an exposition of logical atomism and the Zusammenhangen thesis is given. The way in which the problem appears is then briefly exposed. The way towards a solution begins with the elucidation of Wittgenstein's picture theory of meaning and the truthfunctional analysis of a proposition. The problem is clarified in the question which now arises: i.e., given the truth-functional analysis of a proposition,. how can one proposition be generated out of another? The problem is then shown to vanish in the logical construction of a proposition and of propositions.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Wittgenstein, Ludwig, 1889-1951.; Wittgenstein, Ludwig, 1889-1951. Tractatus logico-philosophicus.; Logical atomism; Ontology